Intelligent technologies in electronic geodetic systems for public spatial management: evolution from automation to digital ethical standards - Dorozhko, Ye.; Udovenko, I. (Land Management, Cadastre and Land Monitoring, 2025)
The article is devoted to the intellectualization of electronic geodetic instruments (EGI) and the development of conceptual foundations for integrating artificial intelligence (AI) technologies into the geoinformation environment (GIS) to enhance the efficiency of spatial management systems. The study presents a developed architectural model of an intelligent spatial management system, which includes the interaction of electronic instruments, sensor modules, GIS platforms, and analytical AI services. The proposed concept of EGI intellectualization is based on three main vectors: autonomy of the measurement process (through machine learning, ML, for object recognition and self-diagnostics), adaptability to environmental conditions (via environmental impact correction and noise reduction), and integrativity with GIS. The research describes the use of AI methods, including deep neural networks (YOLO, Mask R-CNN, U-Net, PointNet) for automatic detection and classification of objects in images and point clouds, as well as for real-time evaluation and correction of GNSS errors using neuro-Kalman filters. The practical directions of model implementation include automated monitoring of engineering structure deformations and intelligent UAV data processing for updating topographic maps. According to the findings, the phased integration of AI transforms EGI into intelligent sensors capable of autonomously assessing data quality and interacting with GIS, thereby providing a reliable foundation for smart cities and sustainable territorial development.Keywords: intellectualization, artificial intelligence (AI), electronic geodetic instruments (EGI), GIS environment, spatial management systems, object detection, GNSS correction.
Keywords: intellectualization; artificial intelligence (AI); electronic geodetic instruments (EGI); GIS environment; spatial management systems; object detection; GNSS correction